Catalytic enantioselective conjugate addition of grignard reagents to cyclic enones using C 1 -1,1′-bisisoquinoline-based chiral ligands - Judeh, Zaher M. A. (2013)
New highly constrained chiral C1-1,10-bisisoquinoline ligands were examined in the enantioselective conjugate addition of Grignard reagents to cyclohexenone and cyclopentenone. The desired 1,4-adducts were obtained in excellent yield and moderate enantiomeric excess (up to 35%).